(untitled) (Progress Annals: Journal of Progressive Research, 2025)
This article highlights the technological and quality significance of the carding process in the yarn spinning industry. Carding is a crucial stage that serves to improve yarn quality by cleaning fibers from foreign impurities, aligning them parallel, and separating short fibers. Yarns produced from carded fibers are distinguished by their strength, flexibility, and uniform structure. This leads to increased durability, aesthetic appearance, and overall production efficiency of the final products. The article also discusses modern carding machines (such as brands like Rieter, Trützschler, and Marzoli) and their role in manufacturing. Research findings indicate that a high-quality carding process plays a vital role not only in yarn quality but also in the smooth and efficient execution of subsequent technological stages.